The effects of impacts on the cooling rates of iron meteorites - Lyons,RJ; Bowling,TJ; Ciesla,FJ; Davison,T; Collins,G (Meteoritics and Planetary Science, 2019)
Iron meteorites provide a record of the thermal evolution of their parent bodies, with cooling rates inferred from the structures observed in the Widmanstätten pattern. Traditional planetesimal thermal models suggest that meteorite samples derived from the same iron core would have identical cooling rates, possibly providing constraints on the sizes and structures of their parent bodies. However, some meteorite groups exhibit a range of cooling rates or point to uncomfortably small parent bodies whose survival is difficult to reconcile with dynamical models. Together, these suggest that some meteorites are indicating a more complicated origin. To date, thermal models have largely ignored the effects that impacts would have on the thermal evolution of the iron meteorite parent bodies. Here we report numerical simulations investigating the effects that impacts at different times have on cooling rates of cores of differentiated planetesimals. We find that impacts that occur when the core is near or above its solidus, but the mantle has largely crystallized can expose iron near the surface of the body, leading to rapid and nonuniform cooling. The time period when a planetesimal can be affected in this way can range between 20 and 70 Myr after formation for a typical 100 km radius planetesimal. Collisions during this time would have been common, and thus played an important role in shaping the properties of iron meteorites.